Social change Among Bushmen of the Eastern Ghanzi Ridge - Silberbauer, G. (My University, 2011)
Pre-settlement culture: Hunting and gathering bands, each occupying and exploiting the resources of recognised, defined territory. Although politically autonomous, bands formed loose alliances for trading, mutual support in times of drought, and visiting. The band was an open community without exclusive qualifications for membership. It was egalitarian and was ordered by a consensus policy. Leadership was ephemeral and non-authoritarian; it rotated among band members. Members were linked by bonds of real and fictive kinship. The kinship system provided a framework for the ordering of relationships and for social control within, and between bands.
African Studies Seminar series. Paper presented June 1974
Keywords: San (African people). Botswana